Fiber Bragg Grating Distributed Chemical Sensors. (2016) - Boersma, Arjen; Cremers, Ray; Jansen, Rob
Abstract: The functionalization of optical fibers containing Fiber Bragg Gratings is a very interesting approach in the development of distributed chemical sensors. We have shown a large variety of coatings, ranging from polymers to ceramics as responsive layers for the detection of many chemical species. Some coated fibers can be applied in extreme conditions, where the presence of oil, water or gaseous hydrocarbons needs to be monitored. Others can be very accurate in the detection of salt concentrations, pH or relative humidity in very small spaces. The small size (250 μm in diameter) is one of the advantages of these types of sensors, together with the multiplexing ability, and absence of electronics.